A Machine in the Forest
Sobre el Centro de Innovación y Tecnología diseñada por Arquitectónica and Ward/Hall Associates.
Keywords: ARQUITECTONICA; WARD, BASIL; WARD HALL ASSOCIATES; ESTADOS UNIDOS; VIRGINIA; HERNDON; CENTROS DE INVESTIGACION